PENGARUH LOKASI, KUALITAS PELAYANAN, FASILITAS TERHADAP KEPUASAN KONSUMEN DI FOTOCOPY DAN PRINT FIRA KEDIRI - Novianti, Erika; Suhardi (Universitas Nusantara PGRI Kediri, 2022)
This study is motivated by competition in the photocopying and printing service business, which is getting tighter daily and will indirectly affect businesses in the service sector in maintaining competition. Therefore, consumer satisfaction in using photocopy and print services is influenced by several factors, including the location of service quality and facilities. This study aims to determine and analyze location, service quality, and facilities' significant influence on customer satisfaction in Photocopy and Print FIRA Kediri. The approach used in this study is a quantitative approach with causal research techniques where the method of collecting data by spreading questionnaires. The technique in sampling uses non-probability techniques. The test tools used in this study are classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing with IBM SPSS statistical software version23. The results of this study show that location, quality of service, and facilities have a significant effect on customer satisfaction.